Food and Culture: An Anthropological Study of Culinary Traditions - I Nyoman Trisutaguna; Layla Abdelrahman; Ramli Ramli (Yayasan Adra Karima Hubbi, 2025)
Background. Food plays a central role in shaping cultural and social identities across different societies. Beyond its biological necessity, food serves as a symbolic expression of heritage, tradition, and belonging. In contemporary society, globalization, urbanization, and migration have increasingly influenced culinary traditions, transforming both local cuisines and the cultural meanings attached to food. Understanding the relationship between food and culture offers valuable insights into how identity and social belonging are negotiated and expressed through everyday practices. Purpose. Explore how culinary traditions are shaped, maintained, and transformed in response to processes such as globalization, urbanization, and migration. Specifically, it examines how social and economic factors influence food choices and the social meanings attached to food in different cultural contexts. Furthermore, this study investigates how food functions as a cultural and social symbol, reflecting and shaping collective identities and social boundaries. Method. The study employs a qualitative research approach using thematic analysis. Data collection methods include in-depth interviews with community members and culinary practitioners, participatory observations in domestic and public food settings, and document analysis of culinary texts, menus, and historical records. This multi-method approach allows for an in-depth understanding of the cultural and social dimensions of food across different communities. Results. The findings reveal that food holds deep symbolic significance across cultures. Culinary traditions serve not only as expressions of cultural heritage but also as markers of social identity, reflecting class, ethnicity, and regional affiliations. Globalization and migration introduce new ingredients and techniques, blending culinary traditions while preserving symbolic meaning. Conclusion. Food is more than just sustenance; it is a powerful cultural and social symbol embedded in everyday life. Social and economic factors shape food choices and meanings, highlighting the dynamic relationship between food, identity, and cultural change. This study contributes to anthropological research on food culture in a globalized world.